1996
DOI: 10.1073/pnas.93.6.2528
|View full text |Cite
|
Sign up to set email alerts
|

The role of DT-diaphorase in the maintenance of the reduced antioxidant form of coenzyme Q in membrane systems.

Abstract: The experiments reported here were designed to test the hypothesis that the two-electron quinone reductase DT-diaphorase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
151
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(158 citation statements)
references
References 37 publications
5
151
1
1
Order By: Relevance
“…NADH-AFR reductase, a trans-oriented activity shows a strong dependency on the CoQ status of the PM, and NQO1 also contribute to the PMRS and are responsive to oxidative stress and aging (29,58). mechanism for reducing PM-associated oxidative stress and, in compensating for mitochondrial dysfunction, as an alternative source of ATP production by increasing NAD levels and glycolysis (28,29). The biochemical characteristics of this system, mainly the dependence on intracellular NADH and CoQ as an electron transfer intermediary, sets it apart from the NOX 1-5 family of enzymes (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NADH-AFR reductase, a trans-oriented activity shows a strong dependency on the CoQ status of the PM, and NQO1 also contribute to the PMRS and are responsive to oxidative stress and aging (29,58). mechanism for reducing PM-associated oxidative stress and, in compensating for mitochondrial dysfunction, as an alternative source of ATP production by increasing NAD levels and glycolysis (28,29). The biochemical characteristics of this system, mainly the dependence on intracellular NADH and CoQ as an electron transfer intermediary, sets it apart from the NOX 1-5 family of enzymes (41).…”
Section: Discussionmentioning
confidence: 99%
“…Cells respond to oxidative stress by transferring electrons from NAD(P)H and ascorbate to extracellular free radicals and/or oxidants (26,27). Coenzyme Q10 (CoQ), a key molecule in the PM redox system (PMRS), can be reduced at the PM by either NAD(P)H-quinone oxidoreductase 1 (NQO1) (28) or NADH-cytochrome b5 reductase (b5R) (29). NQO1 is a NAD(P)H-dependent reductase that is translocated to the inner surface of the PM under stress conditions (30).…”
mentioning
confidence: 99%
“…Ubiquinol-10 is known to be regenerated from CoQ 10 by electron transport carriers present in various biomembranes and by some enzymes. Plasma membrane DT-diaphorase has recently been proven to maintain CoQ 10 in its reduced antioxidant state as ubiquinol-10 and to protect membrane components from free radical damage such as lipid peroxidation [24].…”
Section: Discussionmentioning
confidence: 99%
“…NQO1 is an obligate two-electron reductase and is classified as a detoxification enzyme primarily because of its ability to reduce quinone substrates directly to their less toxic hydroquinone derivatives bypassing the redox-cycling semiquinone radical (6,7). NQO1 can also function as an antioxidant enzyme reducing ubiquinone and vitamin E quinone to their antioxidant forms (8,9). We have characterized a polymorphism in NQO1 (NQO1*2) (10,11) and demonstrated that individuals homozygous for the NQO1*2 polymorphism (NQO1*2/*2) have no measurable NQO1 activity (12).…”
mentioning
confidence: 99%